(untitled) (Applied Biological Research, 2011)
An experiment was conducted to study the influence of enzyme and yeast supplementation in broiler chicken fed high fiber diets. Diets comprized of a control diet [6.2% crude fiber (CF) only] and 8.0 or 10.1% CF level supplemented with either enzyme or yeast @ 200 g ton-1feed. No significant effect was noticed on apparent digestibility values of crude protein and ether extract by the addition of enzyme or yeast in treatment groups. The CF digestion and body weight gains were significantly higher in control and 8.0% CF + 200 g enzyme ton-1as compared to other treatments. The results suggested that CF level can be increased upto 8.0% with enzyme supplementation without having deleterious effect in broiler chicken.